2021
DOI: 10.1111/ane.13551
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and immunotherapy in Alzheimer’s disease

Abstract: Microglia are a type of glial cells that play a key role in the repair of damage to the central nervous system (CNS). In the pathological condition of Alzheimer's disease (AD), β‐amyloid peptide and a variety of pro‐inflammatory factors can activate microglia, resulting in the secretion of a variety of inflammatory factors and neurotoxins. This leads to neuronal damage and even apoptosis, thus triggering AD. In contrast, microglia can protect the CNS by phagocytizing Aβ to slow down AD development. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 57 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…AD follows a prolonged, progressive disease course that begins with pathophysiological changes in the brains of affected individuals years before any clinical manifestations are observed [ 2 ]. These pathophysiological changes include the accumulation of toxic species of amyloid-β (Aβ), the development of neurofibrillary tangles of hyperphosphorylated tau protein, and neurodegeneration that may result from uncontrolled activation of microglia in the brain leading to secretion of neurotoxins and inflammatory factors [ 3 5 ]. Individuals harboring such changes may be asymptomatic or may exhibit clinical manifestations varying from memory lapses to severe and debilitating loss of memory and cognitive function [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…AD follows a prolonged, progressive disease course that begins with pathophysiological changes in the brains of affected individuals years before any clinical manifestations are observed [ 2 ]. These pathophysiological changes include the accumulation of toxic species of amyloid-β (Aβ), the development of neurofibrillary tangles of hyperphosphorylated tau protein, and neurodegeneration that may result from uncontrolled activation of microglia in the brain leading to secretion of neurotoxins and inflammatory factors [ 3 5 ]. Individuals harboring such changes may be asymptomatic or may exhibit clinical manifestations varying from memory lapses to severe and debilitating loss of memory and cognitive function [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aβ causes microglia to secrete pro-inflammatory cytokines and neurotoxic substances, including tumor necrosis factor-α (TNF-α), IL-1, IL-6, IFN-γ, and reactive oxygen species [ 69 ]. First, TNF-α is one of the most important pro-inflammatory cytokines in AD [ 70 ].…”
Section: Microglial Responses To Aβ Plaquesmentioning
confidence: 99%
“…In Alzheimer’s disease, the production of pro-inflammatory factors and Aβ can over-activate microglia, secrete inflammatory factors and neurotoxins, and then induce neuronal damage and even apoptosis, thereby triggering Alzheimer’s disease. On the contrary, microglia can also protect the central nervous system by engulfing Aβ, slowing the development of Alzheimer’s disease ( Li et al, 2021 ). Study have shown berberine can inhibit Aβ-induced microglial activation mediated by suppressor of cytokine signaling 1 (SOCS1) ( Guo et al, 2021 ).…”
Section: Therapeutic Effects Of Berberine On Neurodegenerative Diseasementioning
confidence: 99%